The Role of the Merdeka Learning Curriculum in Enhancing Student Independence and Creativity - Athira Nisrina; Elisa Zahra; Novita Sari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Education is a crucial pillar in the development of a nation. The Indonesian government implements the Merdeka Curriculum to improve the quality of education, emphasizing aspects of independence, creativity, and the development of students' potential. This curriculum provides opportunities for students to determine learning methods that suit their needs and interests, while also encouraging the strengthening of critical thinking skills and the ability to collaborate. This research uses a literature study method to examine the role of the Merdeka Curriculum in enhancing students' independence and creativity. The study reveals that this curriculum has significant potential in shaping a generation capable of overcoming various challenges that may arise in the future.